Analysis of OCR’s Factor and Sales Promotion on E-commerce - Nuruni Ika Kusuma Wardhani; Wilma Cordelia Izaak; Muhammad Ricki Yohanes (Journal of Economics, Business, and Government Challenges, 2020)
Indonesia one of the country with the fastest e-commerce growth in 78% of the world, demanding an unavoidable tight e-commerce business competition, thus encouraging some e-commerce to increase promotion and assessment from customers to be more attractive. The convenience offered by e-commerce attracts consumers to move from offline shopping to online shopping. Many factors influence consumers to switch from offline to online shopping, one of it is online customer reviews and sales promotions. The purpose of this study was to determine the effect of online customer reviews and sales promotions on purchasing decisions at the Bukalapak marketplace. The sample of this study was 99 respondents who were measured using Partial Least Square (PLS) analysis. The results of this study indicate that online customer reviews and sales promotions have a positive and significant effect on buying decisions.